MENGKRITISI LAPORAN KEUANGAN MASJID BERDASAR PSAK 45 DAN 109 - Media Kusumawardani; Muhammad Farhan; Desri Yanto; Fera Widyanata (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study discusses the description of mosque financial statements. The purpose of this study is to determine whether the mosque has implemented the preparation and reporting of mosque finances in accordance with the standards. The standard adopted is PSAK 45 and PSAK 109. In addition, this study also wants to explore the preparation and reporting of mosque finances and the role of the management in developing the mosque financial compilation and reporting. The object of this research is four different types of mosques in Palembang. These mosques are the Historical Mosque, the Great Mosque, the Great Mosque, and the Public Sector Mosque. The type of data used are primary and secondary data. Primary data is obtained based on interview respondents, while secondary data is obtained from the financial statements of each mosque. In this study it was found that all the mosques contained in this study did not apply the PSAK 45 and PSAK 109 standards. Financial preparation and reporting is limited to cash flow statements. While the management's role in developing mosque financial reports has not been meaningful enough to make mosque financial reports according to standards based on PSAK 45 and PSAK 109.